KEEFEKTIFAN KERJASAMA ANTARLEMBAGA DALAM OPERASI PEMULIHAN TERHADAP BENCANA ALAM: STUDI EMPIRIS DI YOGYAKARTA DAN JAWA TENGAH - Purnomo, Hadi; Utomo, Hargo (Journal of Indonesian Economy and Business, 2008)
This study examines the effectiveness of interagency cooperation in the natural disaster recovery operation. This includes an investigation of the extent to which the situational factors (leadership, communication, trust, and commitment) influence interagency processes and outcomes. These factors reflect the behavioral aspect of interagency cooperation.Data were collected through a survey followed by semi-structured interviews to representatives of both governmental and non-governmental organizations involved in the disaster recovery operation of the post earthquake in Yogyakarta and Central Java. Several hypotheses were proposed and tested to assess the magnitude and significance of the observed variables.The result indicates different level of perceived attainment amongst organizations involved in the disaster recovery operations. The behavioral aspects of the organizational leaders were significantly influenced the cooperation processes, which leads to inter-agency outcomes. The main contribution of this study is its presentation and empirical evidence of the proposed model of inter-agency cooperation.Key Words: effectiveness, interagency cooperation, disaster recovery